2004
DOI: 10.1002/jmv.20218
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive and specific detection of strains of Japanese encephalitis virus using a one‐step TaqMan RT‐PCR technique

Abstract: A rapid, sensitive, and accurate laboratory diagnostic test is needed for distinguishing Japanese encephalitis virus (JEV) from other diseases featuring similar clinical symptoms and also for preventing potential outbreaks. In this study, a TaqMan reverse transcription (RT)-polymerase chain reaction (PCR) assay was developed for rapid detection and quantification of the viral RNA of various JEV strains. A consensus JEV NS3 region was chosen to design the primers and the TaqMan probe. The JEV TaqMan assay used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…cDNA synthesis was performed using Omniscript Reverse Transcription System (Qiagen) using random hexamers as per manufacturer’s instructions. 100 ng of cDNA was used to determine JEV genome copy numbers using Taqman quantitative RT-PCR reagent (Life Technologies) using primers and probe described previously [20]. 200 ng of cDNA was used for detection of various genes using Fast SYBR Green quantitative RT-PCR reagent (Life Technologies) using primers as listed in Table S1.…”
Section: Methodsmentioning
confidence: 99%
“…cDNA synthesis was performed using Omniscript Reverse Transcription System (Qiagen) using random hexamers as per manufacturer’s instructions. 100 ng of cDNA was used to determine JEV genome copy numbers using Taqman quantitative RT-PCR reagent (Life Technologies) using primers and probe described previously [20]. 200 ng of cDNA was used for detection of various genes using Fast SYBR Green quantitative RT-PCR reagent (Life Technologies) using primers as listed in Table S1.…”
Section: Methodsmentioning
confidence: 99%
“…To date, several studies have detected latent JEV in the body of mosquitoes using real-time PCR (19), and in the serum of humans, pigs, and mice (8,21,25). DENV has been reported to be detected by RT-LAMP in the serum of DENV-infected patients (16).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several investigators have reported polymerase chain reaction (PCR)-based detection systems for the rapid detection of JEV infection in clinical specimens that were negative for viral isolation, suggesting that nucleic acid-based assays hold greater promise for the detection of JEV infection. In addition to traditional reverse transcription-polymerase chain reaction (RT-PCR), more rapid and sensitive real-time PCR-based assays, such as TaqMan RT-PCR, nucleic acid sequence-based amplification (NASBA) and branched-DNA methods, have been reported and are currently under extensive evaluation with human and field mosquito samples (8,19,21,25) However, these assays usually take 2-3 hr.…”
mentioning
confidence: 99%
“…Standard curve was generated using in vitro transcribed JEV-NS3 from a plasmid clone. Viral genome copy numbers were estimated using NS3 primer and probe set described previously [9]. GAPDH was used for normalization of the samples (Forward primer: 5′- TGTGTCCGTCGTGGATCTGA - 3′ Reverse primer: 5′- CCTGCTTCACCACCTTCTTGA - 3′ Taqman probe: 5′-FAM-CCGCCTGGAGAAACCTGCCAAGTATG-TAMRA).…”
Section: Methodsmentioning
confidence: 99%